2022
DOI: 10.20944/preprints202206.0024.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of Willingness of the General Public to Receive a Second COVID-19 Booster Dose or a New COVID-19 Vaccine: A Cross-Sectional Study in Greece

Abstract: Given the concerns of waning immunity from the primary COVID-19 vaccines and the first booster dose, we conducted an on-line cross-sectional study in May 2022 to investigate willingness to receive a second COVID-19 booster dose or a new COVID-19 vaccine and its associated factors. Overall, 22.7% of participants were willing to be vaccinated, 39.3% were unsure, but tend to be willing, 25.8% were unsure, 4.9% were unsure, but tend to be unwilling, and 7.4% were unwilling to be vaccinated. The main reasons agains… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
1
3
1
Order By: Relevance
“…On the other hand, the crude regression analysis indicated that fear of adverse effects of the vaccine is one of the reasons for a lower IBV. This aligns with many studies that concluded that concern about adverse effects was the main factor for refusal or hesitancy to receive a booster dose ( Qin et al, 2022 ; Rzymski, Poniedziałek & Fal, 2021 ; Folcarelli et al, 2022 ; Galanis et al, 2022 ; Lounis et al, 2022 ). However, in the adjusted model, no such association was observed, possibly because this effect may have been overshadowed by the recommendation of physicians and other health professionals.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, the crude regression analysis indicated that fear of adverse effects of the vaccine is one of the reasons for a lower IBV. This aligns with many studies that concluded that concern about adverse effects was the main factor for refusal or hesitancy to receive a booster dose ( Qin et al, 2022 ; Rzymski, Poniedziałek & Fal, 2021 ; Folcarelli et al, 2022 ; Galanis et al, 2022 ; Lounis et al, 2022 ). However, in the adjusted model, no such association was observed, possibly because this effect may have been overshadowed by the recommendation of physicians and other health professionals.…”
Section: Discussionsupporting
confidence: 84%
“…Studies conducted in China ( Qin et al, 2022b ; Tung et al, 2019 ; Hu et al, 2022 ), Malaysia ( Abdullah, Ching & Ali, 2023 ) and Czech Republic ( Klugar et al, 2021 ), as well as a systematic review ( Abdelmoneim et al, 2022 ), indicated that the perceived efficacy or effectiveness of vaccines was associated with IBV of the booster dose. On the other hand, studies conducted in China ( Lai et al, 2021 ; Qin et al, 2022 ) and countries such as Poland ( Rzymski, Poniedziałek & Fal, 2021 ), Italy ( Folcarelli et al, 2022 ), Greece ( Galanis et al, 2022 ), and Algeria ( Lounis et al, 2022 ) reported that the reasons for refusing to receive the booster dose were uncertainty about its efficacy and the perception that an additional dose was not necessary. It should also be considered that these studies were conducted at different times during the COVID-19 pandemic, which could result in variations in the results, as the perception of the population may have changed over time.…”
Section: Discussionmentioning
confidence: 99%
“…This study found a positive association of side-effects with female sex, younger age, and brand of the vaccine. (35) In our study, we did not nd an association between age and side-effects. Consistent with existing literature, we found a strong association of our outcome with female sex, and a weak association with vaccine dose, and a recent COVID-19 infection.…”
Section: Discussioncontrasting
confidence: 64%
“…A study found that men's desire was 2.5 times higher than women's (23). Female desire may be lower due to psychological gender differences (24), aversion to novel medical technology (25), and belief in vaccine-fertility myths shared on social media (26,27). The highest willingness to receive the vaccine was observed in the age group over 60.…”
Section: Discussionmentioning
confidence: 99%
“…According to a review study, eight out of 12 studies reported a significantly higher likelihood of older individuals accepting the first booster dose of the vaccine (23). The greater tendency in older adults may be due to the high probability of getting a severe form of the disease, hospitalization, and mortality due to COVID-19 (24). People with an underlying condition were more likely to get a booster dosage, while unwillingness in healthy individuals was also found (4).…”
Section: Discussionmentioning
confidence: 99%